Examining gender issues in education: exploring confounding experiences on three female educators’ professional knowledge landscapes - Kelley, Michaelann; Craig, Cheryl J.; Curtis, Gayle A. (Frontiers in Education, 2023)
Business sources report that it will take 124 years for females to achieve parity in the workforce. Parity relates to compensation but also includes working conditions. The latter topic is taken up in this article using narrative inquiry as our method of investigation. Narrative inquiry—inquiring into narratives—employs three research tools: broadening, burrowing and storying/re-storying. To these tools, fictionalization, a fourth tool, is added. This is because the interwoven cases involve easily identifiable others and precautions need to be taken. This article discusses gender matters lived and told, and re-lived and re-told, over the career continuum of three women who have worked in public school and university settings. As females, they periodically encountered situations where they were perceived, interpreted, and responded to differently than males. The article looks at early, mid, and recent career challenges experienced in the female educators’ places of work. This research looks backward, forward, inside, and out through processes of individual and group reflection. It begins with bio-sketches, which were prepared individually. After that, the aforementioned research tools are used to unpack early, middle, and current career happenings. Reflective unpacking of the three females’ experiences within a community of critical friendship allowed for greater understanding and meaning-making to occur. The underlying intent of this work is to understand the shaping forces of gender on women’s professional lives—not to name and shame those who got away with acting the ways in which they did. The significance of the work lies in its use of narrative exemplars that are transparent, have a ring of authenticity to them, and promote trustworthiness and relatability when shared with others.